2012
DOI: 10.1039/c2dt31222k
|View full text |Cite
|
Sign up to set email alerts
|

Structural, spectroscopic and redox properties of a mononuclear CoII thiolate complex – the reactivity toward S-alkylation: an experimental and theoretical study

Abstract: The structural, spectroscopic, redox properties and also the reactivity toward S-alkylation of a new mononuclear N2S2 dithiolate Co(II) complex [CoL] (1), with H(2)L = 2,2'-(2,2'-bipyridine-6,6'-diyl)bis(1,1-diphenylethanethiol), have been investigated. The X-ray structure of 1 has revealed an unusual distorted square planar geometry for a Co(II) ion within a thiolate environment. The X-band EPR spectrum of displays a rhombic S = 1/2 signal consistent with a low spin configuration for the d(7) Co(II) ion with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 64 publications
5
14
0
Order By: Relevance
“…Each Co II ion displays a highly distorted square-pyramidal geometry, with two N atoms and two m-S atoms of the ligand forming the square planar base and one S atom of the disulfide bridge in axial position. As expected, the axial Co II ÀS S-S bond (2.5341 (8) ) is significantly longer than the basal Co II À (m-S thiolate ) bonds (2.3796(8) and 2.3272 (7) ), the latter being in the expected range (2.21-2.39 ). [10] The long distance between the two Co ions (3.1188(5) ) implies the absence of a direct metal-metal bond.…”
Section: Methodssupporting
confidence: 75%
See 4 more Smart Citations
“…Each Co II ion displays a highly distorted square-pyramidal geometry, with two N atoms and two m-S atoms of the ligand forming the square planar base and one S atom of the disulfide bridge in axial position. As expected, the axial Co II ÀS S-S bond (2.5341 (8) ) is significantly longer than the basal Co II À (m-S thiolate ) bonds (2.3796(8) and 2.3272 (7) ), the latter being in the expected range (2.21-2.39 ). [10] The long distance between the two Co ions (3.1188(5) ) implies the absence of a direct metal-metal bond.…”
Section: Methodssupporting
confidence: 75%
“…As expected, the Co À S and the CoÀN bonds in 1 are slightly longer than those in [Co II LS]. [8] From the magnetic properties of 1, it can be concluded that it is an S = 1 Co III species both in solid state and in solution. The c T product at 320 K of 1.3 cm 3 K mol À1 (Figure 2) is in agreement with the expected values for such S = 1 species.…”
supporting
confidence: 67%
See 3 more Smart Citations